An automated stochastic approach to the identification of the protein specificity determinants and functional subfamilies - Mazin, Pavel V.; Gelfand, Mikhail S.; Mironov, Andrey A.; Rakhmaninova, Aleksandra B.; Rubinov, Anatoly R.; Russell, Robert B.; Kalinina, Olga V. (Algorithms for molecular biology, 2010)
Recent progress in sequencing and 3 D structure determination techniques stimulated development of approaches aimed at more precise annotation of proteins, that is, prediction of exact specificity to a ligand or, more broadly, to a binding partner of any kind.
Gesehen am 30.03.2023